2017
DOI: 10.1136/bmjqs-2017-006610
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the association between Nursing Home Survey on Patient Safety culture (NHSOPS) measures and catheter-associated urinary tract infections: results of a national collaborative

Abstract: This large national collaborative of nursing homes saw declining CAUTI rates as well as improvements in several NHSOPS domains. However, no association was found between initial or over-time NHSOPS scores and CAUTI rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 50 publications
5
43
0
Order By: Relevance
“…and 'compliance with procedures' dimensions are the priority areas to be improved in nursing homes, as they had the lowest scores and the lowest PRRs. A similar situation was found in other countries, such as the USA (Smith et al, 2018), Belgium (Desmedt et al, 2018) and Norway (Ree & Wiig, 2019). The majority of staff are reported to be under-educated, lack experience and are only temporarily employed, which was confirmed in a similar study (Yang et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…and 'compliance with procedures' dimensions are the priority areas to be improved in nursing homes, as they had the lowest scores and the lowest PRRs. A similar situation was found in other countries, such as the USA (Smith et al, 2018), Belgium (Desmedt et al, 2018) and Norway (Ree & Wiig, 2019). The majority of staff are reported to be under-educated, lack experience and are only temporarily employed, which was confirmed in a similar study (Yang et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, the relationship between patient safety culture and adverse events in nursing homes remains controversial. Some studies reported that an improvement in safety culture was associated with a decrease in rates of adverse events (Abusalem et al, 2019;Li et al, 2019), but no association found between them in a large national collaborative study (Smith et al, 2018…”
Section: Discussionmentioning
confidence: 97%
“…Despite this vulnerability among nursing home patients, most of the patient safety research has so far focused on hospital settings as reflected in the literature [8][9][10][11][12]. Literature regarding patient safety issues in primary care [13] and LTC settings and especially in nursing homes is currently emerging [14][15][16][17][18][19], yet there is an urgent need for more studies in diverse contexts. Some current studies indicate that a positive patient safety culture is associated with patient safety outcomes such as reports of falls and restraint use, though the findings are not consistent [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Literature regarding patient safety issues in primary care [13] and LTC settings and especially in nursing homes is currently emerging [14][15][16][17][18][19], yet there is an urgent need for more studies in diverse contexts. Some current studies indicate that a positive patient safety culture is associated with patient safety outcomes such as reports of falls and restraint use, though the findings are not consistent [14][15][16]. In a recent study of staff perceptions of patient safety culture in Norwegian nursing homes, we found a positive awareness of patient safety culture among frontline staff together with an established confidence in nursing managers' attention to patient safety issues [17].…”
Section: Introductionmentioning
confidence: 99%
“…Per the recently enacted Patient Safety Act, Korea has also established an external reporting system to which relevant hospitals report patient safety incidents. The 'Patient Safety Reporting Learning System' was utilized as evidence for governmental policymaking and macroscopic improvement activities to enhance patient safety and quality of care by establishing and analyzing a patient safety information database, containing data electronically submitted by hospitals [50]. The reporting system for LTC facilities should also be reinforced to examine the state of safety incidents and relevant problems, based on which appropriate safety improvement activities should be launched.…”
Section: Discussionmentioning
confidence: 99%